Analisis minat masyarakat dalam berinvestasi sukuk - Nita Andriyani Budiman (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
This study aims to analyze public interest in investing in sukuk seen from investment risk factors(risk of default, interest rate, risk of repurchase, investment costs, deposits, liquidity, inflation,and competitiveness) and islamic attribute factors (avoiding usury, avoiding rental investment,avoiding uncertainty, equitable investment, good luck deals, activities in accordance with sharia,not wrongdoing and tyranny, and profit sharing systems). The population in this study were investorswho had SR-010 registered at the Kudus selling agent. The sampling technique used conveniencesampling technique and found 48 people as research respondents. The analysis method used ismultiple linear regression analysis. The results of this study indicate that investment risk factorsand islamic attribute factors influence the interest of the community to invest in sukuk..